The Development of Maha Mas Medic Services Sdn.Bhd Employee Management System - Mohamad Irfan Abdul Muthalif,; Ruhaya Binti Ab. Aziz, (Applied Information Technology And Computer Science, 2025)
Maha Mas Medic Services Sdn. Bhd., an ambulance provider in Selangor and Kuala Lumpur, faces inefficiencies and resource wastage using Excel for staff management. Issues include time-consuming processes, overstaffing, missed schedules, and potential salary calculation errors. To address these, a web-based Employee Management System is proposed. The objectives are to analyze and design the system using an object-oriented approach, develop it as a web-based application, and test its functionality and usability through alpha and beta testing. The development process follows a prototyping model, using tools like Visual Studio Code and phpMyAdmin, aiming to streamline operations, enhance accuracy, and improve overall efficiency. The system will give administrators control over user accounts, staff, schedules, salaries, and ambulances, while allowing staff to view schedules, check salaries, and request changes. Notifications will alert users to schedule updates and requests.